A new efficient flow continuity lubrication model for the piston ring-pack with consideration of oil storage of the cross-hatched texture. (March 2018) - Hu, Yang; Meng, Xianghui; Xie, Youbai
Abstract: In this paper, a new efficient flow continuity lubrication model for the piston ring -pack is established by taking the oil storage of the cross-hatched texture into account. To fully consider the influence of the cross-hatched texture and plateau roughness on the lubrication and oil transport, a two-dimensional two-scale mass-conserving homogenized mixed lubrication model is developed. To solve the mass-conserving model efficiently, the recently proposed Fischer-Burmeister-Newton-Schur (FBNS) algorithm is adopted. The oil available to lubricate each ring is determined by conducting an oil transport analysis. The trapped oil in the texture is calculated as an extra oil supply to the inlet of the contact. The developed model has great potential for understanding and optimizing the honed cylinder liner surface. Highlights: A new efficient flow continuity lubrication model for the ring-pack is established. The oil storage of the cross-hatched texture is taken into account. A two-scale mass-conserving homogenized mixed lubrication model is developed. The FBNS algorithm is used to solve the cavitation model efficiently. The oil available to each ring is determined by the analysis of oil transport.